Auricular Acupressure for Insomnia in Patients With Maintenance Hemodialysis: A Systematic Review and Meta-Analysis - Pei, Ming; Chen, Junli; Dong, Shuo; Yang, Bo; Yang, Kang; Wei, Lijuan; Zhai, Jingbo; Yang, Hongtao (Frontiers in Psychiatry, 2021)
Background: Insomnia is one of the common problems in patients with maintenance hemodialysis (MHD). Previous studies have reported the beneficial effects of auricular acupressure (AA) for insomnia in patients with MHD. This study aimed to critically evaluate the efficacy and safety of AA for insomnia in patients with MHD. Methods: Web of Science, Embase, PubMed, Cochrane Library, Chinese Biomedical Database, Wanfang Data, Chinese Science and Technology Periodicals database, and China National Knowledge Infrastructure were systematically searched from inception to April 30, 2020 to identify any eligible randomized controlled trials. MHD patients with insomnia were included regardless of age, gender, nationality, or race. The experimental interventions included AA alone or AA combined with other therapies. The control interventions included placebo, no treatment, or other therapies. The primary outcome was sleep quality measured by the Pittsburgh Sleep Quality Index (PSQI). RevMan 5.3 software was used for statistical analysis. Results: Eight studies involving 618 participants were included for statistical analysis. A meta-analysis showed no significant difference of PSQI global score after eight weeks of AA treatment compared with estazolam (P = 0.70). Other narrative analyses revealed that PSQI global score was significantly attenuated after AA treatment in comparison with mental health education (P = 0.03, duration of four weeks; P = 0.02, duration of eight weeks), AA plus routine nursing care compared with routine nursing care alone (P < 0.0001), AA plus footbath compared with footbath alone (P = 0.01), respectively. A meta-analysis showed that AA could significantly increase the response rate (reduction of PSQI global score by 25% and more) in comparison with estazolam (P = 0.01). Other narrative analyses reported that the response rate was significantly increased after AA treatment compared with sham AA (P = 0.02), AA compared with mental health education (P = 0.04), AA plus routine nursing care compared with routine nursing care alone (P = 0.0003), respectively. Conclusion: The present findings suggest that AA may be an alternative treatment for insomnia in patients with MHD. However, more large-scale, high-quality trials are still warranted to confirm these outcomes.